(untitled) (Philology, 2026)
The main goal of this work is to offer some possible conceptual explanations for the apparent estrangement between the scientific fields of Geography and American Studies. For this purpose, it discusses the relationship between the above academic subjects in terms of the similarities and differences in how they constitute their objects of study. The author uses an interdisciplinary approach and comparative analysis of their research content and determines that it is quite inefficient at best to rediscover “America” yet again. The conclusion posits that, rather than overlooking existing knowledge, it is of crucial importance for the American Studies field, as well as any other Area Studies field, to use the scientific insights, methodological experience, approaches, and results of the science of Geography.